Fremgangsmåder til reduktion af serumniveauer af Fc-indeholdende midler ved anvendelse af FcRn-antagonister - ULRICHTS, Peter; ONGENAE, Nicolas, G.h; BLANCHETOT, Christophe; DE HAARD, Johannes; DREIER, Torsten (2021)
Provided are novel methods of reducing the serum levels of Fc-containing agents (e.g., antibodies and immunoadhesins) in a subject. These methods generally comprise administering to the subject an effective amount of an isolated FcRn-antagonist that binds specifically to FcRn with increased affinity and reduced pH dependence relative to the native Fc region. The disclosed methods are particularly useful for treating antibody-mediated disorders (e.g. autoimmune diseases).